STRATEGI PEMASARAN BERBASIS DIGITAL SYARIAH DALAM PROMOSI PRODUK DI BANK SYARIAH INDONESIA - Ramadlan, Syahru; Sopingi, Imam; Nur Hanifah, Erma (LPPM Universitas KH. A. Wahab Hasbullah, 2024)
The purpose of this study is to determine and explain the sharia-based digital marketing strategy used to promote products at Bank Syariah Indonesia (BSI) KCP Pasuruan Balaikota. In today's digital era, BSI must utilize technology to promote its sharia-compliant products to a wider audience, while adhering to sharia principles. This research uses a case study method with a qualitative approach. Data were collected through observation, in-depth interviews, and documentation. This study found that BSI KCP Pasuruan Balaikota uses different digital strategies such as social media, mobile banking application, and official website to promote and educate customers. BSI also considers sharia compliance in marketing materials and works with sharia influencers to build public trust. This method has been successful in increasing customer knowledge and interest in shariah-compliant products. According to this study, using organized and shariah-compliant digital marketing can be a better option to advertise Islamic banking products in Indonesia.